Феномен «двудомности» творчества писателей (на материале югославянских литератур) (Filološke studije, 2019)
The problem of «diclnousess» literary creativity inthe multinational environment, that means its double literary accessory, hasalready the history. In a basis of its occurrence lay deep geopolitical,ethnic, linguistic, religious and historical-literary roots.